Islam and the securitisation of population policies Muslim states and sustainability - Riddell, Katrina (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2009)
Discussing contemporary population discourses and their historical foundations, this book examines how population growth has become an international security issue. Using Pakistan and Iran as examples, it provides a nuanced understanding of Muslim states' interaction with global debates on sustainability